Rancang Bangun Sistem Informasi Pendaftaran Magang Berbasis Web di Diskominfo Kabupaten Tegal - Salma Nafisa Qurrotu’Aini; Slamet Wiyono; Zaenul Arif (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
The internship registration process at the Communication and Information Office of Tegal Regency is still carried out manually, resulting in several problems, such as lengthy registration procedures, difficulties in managing and retrieving data, and the risk of document loss. This study aims to design and develop a web-based internship registration information system that supports the registration, verification, selection, and information delivery processes in an integrated manner. The system was developed using the Waterfall method, which consists of requirements analysis, system design, implementation, and testing stages. The application was developed using the Laravel framework and MySQL database. System testing was conducted using the Black Box Testing method to ensure that all system functions operate according to user requirements.The results indicate that the developed system can simplify the internship registration process, improve data management efficiency, accelerate the selection process, and provide real-time registration status information to applicants. Based on the testing results, all system features function properly and meet the predetermined functional requirements.